Hydrogenation condensation catalyst with sandwich structure as well as preparation method and application of hydrogenation condensation catalyst

By using a hydrogen -reducing catalyst with a sandwich structure in the amine synthetic catalyst, the platinum nanoparticles are encapsulated in the mezzanine of the inner and outer metal organic frame, which solves the problem of the catalyst activated nanoparticles. Essence

CN119368239APending Publication Date: 2025-01-28THE NAT CENT FOR NANOSCI & TECH NCNST OF CHINA
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411503538.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art has problems in imine synthesis with high cost substrates, high temperature and high pressure conditions, poor conversion efficiency and selectivity, and active nanoparticles of the catalyst are prone to aggregation and loss, affecting catalytic activity and stability.

Method used

The hydrogenation catalyst with the sandwich structure is used to uniformly dispersed the platinum nanoparticles and encapsulate it on the mezzanine of the inner and outer metal organic frame to prevent the falling or aggregation of the platinum nanoparticles, improve the stability of the catalyst, and use the organic framework of platinum nanoparticles and metal organic frameworks. The synergy effect enhances the activity and selectivity of the catalyst.

Benefits of technology

Under mild conditions, high conversion efficiency and highly selectively synthesize amine compounds, improve the stability and activity of catalysts, and significantly improve the yield of raw materials and the yield of target products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368239A_ABST
    Figure CN119368239A_ABST
Patent Text Reader

Abstract

The invention relates to a hydrogenation condensation catalyst with a sandwich structure as well as a preparation method and application thereof. The hydrogenation condensation catalyst with the sandwich structure sequentially comprises an inner layer, an interlayer and an outer layer from inside to outside, the inner layer comprises a first metal organic framework, the interlayer comprises platinum nanoparticles, and the outer layer comprises a second metal organic framework. According to the hydrogenation condensation catalyst with the sandwich structure, the platinum nanoparticles are dispersed and encapsulated in the interlayer of the first metal organic framework and the second metal organic framework, so that the platinum nanoparticles are prevented from falling off or gathering, firm encapsulation and ordered dispersion of the platinum nanoparticles are realized, the stability of the catalyst is improved, and the catalyst has a good application prospect. The platinum nanoparticles in the hydrogenation condensation catalyst with the sandwich structure and the metal organic frameworks on the inner layer and the outer layer have an efficient synergistic effect and can jointly improve the activity and the selectivity of an imine compound prepared through a catalytic hydrogenation condensation reaction, so that the catalyst has excellent conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a sandwich-structured hydrogenation condensation catalyst and a preparation method and application thereof. Background Art

[0002] Imines, compounds containing carbon-nitrogen double bond functional groups, are an important class of organic compounds. They are often used as important intermediates in various industries such as agrochemicals, pharmaceuticals and fine chemicals, and are indispensable in modern organic chemistry. At present, a variety of methods have been developed for the synthesis of imines, such as the condensation of amines and carbonyl compounds under acid catalysis, and the oxidation of secondary amines. However, these methods have many problems in practical applications, including the high cost of amine substrates, the need for drastic reaction conditions such as high temperature and high pressure or special systems such as photocatalysis and electrocatalysis, and poor conversion efficiency (TOF) and selectivity. At present, there is an urgent need to develop a new approach to synthesize imines with high TOF and high selectivity under mild conditions using inexpensive substrates.

[0003] Nitroaromatic compounds are one of the most commonly used starting materials in the synthesis process of imine compounds. For example, nitrobenzene is a common chemical product usually prepared by direct nitration of benzene. It has a wide range of sources and low cost. After nitrobenzene is hydrogenated and reduced to primary amines, N-benzylidene aniline is prepared by condensation reaction, which is an important and promising way to prepare imines. CN103214392A discloses a method for preparing N-benzylidene aniline using a porous carbon material catalyst supported by palladium and nitrobenzene derivatives and benzyl alcohol as raw materials. The substrate can be basically completely converted within 18 hours at 160 ° C, and the selectivity of the target product is as high as 96.7%. However, during the preparation process, the active nanoparticles of the catalyst have the problem of easy aggregation and easy loss, which greatly affects its catalytic activity and stability. Therefore, it is urgent to construct a catalytic system that can stabilize its structure and prevent activity loss. In addition, in order to realize hydrogenation condensation reaction under milder conditions, an effective idea is to construct Lewis acid sites in the catalytic system, which is conducive to promoting the further condensation of the generated amine intermediates, but it also further increases the difficulty of catalyst design.

[0004] In view of the defects of the existing technology, it is an urgent task to provide a high-performance and stable catalyst to achieve high conversion efficiency and high selectivity catalytic reactions under mild conditions. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a sandwich structure hydrogenation condensation catalyst and its preparation method and use. The sandwich structure hydrogenation condensation catalyst provided by the present invention uniformly disperses and encapsulates platinum nanoparticles in the interlayer of the inner and outer metal organic frameworks, prevents the platinum nanoparticles from falling off or agglomerating, improves the stability of the catalyst, and the synergistic effect of the platinum nanoparticles in the sandwich structure hydrogenation condensation catalyst and the inner and outer metal organic frameworks jointly improves the activity and selectivity of the catalyst, so that the catalyst has a better conversion efficiency (TOF).

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a sandwich-structured hydrogenation condensation catalyst, which comprises, from the inside to the outside, an inner layer, an interlayer and an outer layer; the inner layer comprises a first metal-organic framework, the interlayer comprises platinum nanoparticles, and the outer layer comprises a second metal-organic framework.

[0008] The sandwich-structured hydrogenation condensation catalyst provided by the present invention uniformly disperses and encapsulates platinum nanoparticles in the interlayer of a first metal-organic framework and a second metal-organic framework, thereby preventing the platinum nanoparticles from falling off or agglomerating, achieving firm encapsulation and orderly dispersion of the platinum nanoparticles, and improving the stability of the catalyst. In addition, the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst and the metal-organic frameworks arranged in the inner and outer layers have a highly efficient synergistic effect, which can jointly improve the activity and selectivity of the catalyst, thereby making the catalyst have a more excellent conversion efficiency (TOF).

[0009] Preferably, the first metal organic framework and the second metal organic framework each independently comprise a zirconium-based metal organic framework material.

[0010] Preferably, the first metal organic framework and the second metal organic framework are the same, preferably MOF-808.

[0011] The first metal organic framework and the second metal organic framework in the present invention are both MOF-808, which can realize controllable encapsulation of metal nanoparticles and has good thermal stability. Meanwhile, the Zr metal node is beneficial to the effect of the catalyst in catalyzing hydrogenation condensation reaction.

[0012] Preferably, the microscopic morphology of the first metal organic framework of the inner layer is an octahedron, and the diameter of the octahedron is 300-500nm, for example, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm or 500nm.

[0013] Preferably, the average particle size of the platinum nanoparticles is 1-3 nm, for example, 1 nm, 1.2 nm, 1.4 nm, 1.6 nm, 1.8 nm, 2 nm, 2.2 nm, 2.4 nm, 2.6 nm, 2.8 nm or 3 nm, etc., preferably 1.7-2.8 nm.

[0014] Preferably, based on the total mass of the sandwich structure hydrogenation condensation catalyst as 100wt%, the mass percentage of the platinum nanoparticles is 0.2-2wt%, for example, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2.0wt%, etc., preferably 0.4-1.8wt%.

[0015] Preferably, the thickness of the outer layer is 5-40 nm, for example, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm, etc., preferably 5-20 nm.

[0016] In the sandwich-structured hydrogenation condensation catalyst provided by the present invention, if the thickness of the outer layer is too thin, it will not be possible to effectively prevent the platinum nanoparticles from falling off or agglomerating, thereby affecting the stability of the catalyst; if the thickness of the outer layer is too thick, it will hinder the mass transfer of the catalytic reactants to the platinum nanoparticles, thereby significantly reducing the catalytic performance of the catalyst.

[0017] In a second aspect, the present invention provides a method for preparing the sandwich structured hydrogenation condensation catalyst as described in the first aspect, the preparation method comprising the following steps:

[0018] (1) mixing a platinum nanoparticle dispersion with a first metal organic framework, and drying the mixture to obtain a supported material, wherein the supported material includes the first metal organic framework supported with platinum nanoparticles;

[0019] (2) Mixing the support material with a solvent to obtain a support material dispersion, mixing the support material dispersion with a second metal organic framework precursor dispersion and subjecting the mixture to a solvent thermal reaction, followed by separation and drying to obtain the sandwich structure hydrogenation condensation catalyst.

[0020] The method for preparing a sandwich structure hydrogenation condensation catalyst provided by the present invention comprises mixing a platinum nanoparticle dispersion with a first metal organic framework, achieving uniform loading of platinum nanoparticles on the first metal organic framework, and then subjecting the first metal organic framework loaded with platinum nanoparticles to a solvent thermal reaction with a precursor dispersion of a second metal organic framework, thereby in situ growing the second metal organic framework, and then preparing a sandwich structure hydrogenation condensation catalyst. At the same time, the preparation method provided by the present invention can ensure that the platinum nanoparticles of the sandwich are uniformly dispersed and stably encapsulated between the first metal organic framework and the second metal organic framework. The preparation method also has the advantages of easy operation, simple equipment requirements, simple implementation, excellent performance of the synthesized catalyst, etc. The prepared catalyst can more conveniently achieve the synthesis of a specific substance with high yield, high selectivity and high conversion efficiency in a hydrogenation condensation reaction.

[0021] Preferably, the volume mass ratio of the platinum nanoparticle dispersion in step (1) to the first metal organic framework is 1 mL:(10-50) mg, for example, 1 mL:10 mg, 1 mL:15 mg, 1 mL:20 mg, 1 mL:25 mg, 1 mL:30 mg, 1 mL:35 mg, 1 mL:40 mg, 1 mL:45 mg or 1 mL:50 mg, etc.

[0022] In the present invention, if the volume mass ratio of the platinum nanoparticle dispersion to the first metal organic framework is too low, the content of the platinum nanoparticles is low, which will cause the catalytic performance of the catalyst to deteriorate; if the volume mass ratio of the two is too high, it will cause the platinum nanoparticles to aggregate, affecting the catalytic performance of the catalyst.

[0023] Preferably, the mixing time in step (1) is 15-60 min, for example, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min or 60 min, etc.

[0024] Preferably, the mixing time of the support material and the solvent in step (2) is 5-20 min, such as 5 min, 10 min, 15 min or 20 min.

[0025] Preferably, the concentration of the load material dispersion in step (2) is 2-10 mg / mL, such as 2 mg / mL, 4 mg / mL, 6 mg / mL, 8 mg / mL or 10 mg / mL.

[0026] Preferably, the volume ratio of the support material dispersion to the second metal organic framework precursor dispersion in step (2) is (1-8):1, for example 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1, etc., preferably (3-6):1.

[0027] In the present invention, the volume ratio of the support material dispersion to the second metal organic framework precursor dispersion will affect the thickness of the outer layer in the final sandwich structure hydrogenation condensation catalyst, thereby affecting the activity, selectivity and stability of the sandwich structure hydrogenation condensation catalyst.

[0028] Preferably, the temperature of the solvothermal reaction in step (2) is 80-150°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.

[0029] Preferably, the solvent thermal reaction time in step (2) is 15-20 h, for example, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h.

[0030] Preferably, the solvent thermal reaction in step (2) is carried out under oil bath conditions.

[0031] As a preferred technical solution of the present invention, the preparation process of the first metal organic framework in step (1) comprises:

[0032] The first zirconium source, the first organic ligand and the first solvent are first mixed to obtain a first precursor dispersion, the first precursor dispersion is subjected to a solvothermal reaction, and then separated and dried to obtain the first metal organic framework.

[0033] Preferably, the molar ratio of the first zirconium source to the first organic ligand is 3:(0.8-1.2), for example, 3:0.8, 3:0.9, 3:1, 3:1.1 or 3:1.2, etc.

[0034] Preferably, a first regulator is also added during the first mixing process.

[0035] The present invention introduces a regulator into the first metal organic framework, which promotes the coordination of the first zirconium source and the first organic ligand to form the first metal organic framework and regulates the morphology and crystallinity of the obtained first metal organic framework.

[0036] Preferably, the first solvent comprises any one of N,N-dimethylformamide, N,N-diethylformamide or N,N-dimethylacetamide, preferably N,N-dimethylformamide.

[0037] Preferably, the volume ratio of the first solvent to the first regulator is 1:(0.2-1), such as 1:0.2, 1:0.4, 1:0.6, 1:0.8 or 1:1, etc.

[0038] Preferably, in the first precursor dispersion, the concentration of the first zirconium source is 10-100 mmol / L, for example, 10 mmol / L, 20 mmol / L, 40 mmol / L, 60 mmol / L, 80 mmol / L or 100 mmol / L.

[0039] Preferably, the first zirconium source includes any one of zirconium oxychloride octahydrate or zirconium tetrachloride, preferably zirconium oxychloride octahydrate.

[0040] Preferably, the first organic ligand comprises trimesic acid.

[0041] Preferably, the first regulator comprises any one of formic acid, acetic acid, benzoic acid or hydrochloric acid, preferably formic acid.

[0042] In the present invention, formic acid is used as a monodentate ligand in the preparation process of the first metal organic framework, which has the advantage of further optimizing the morphology and crystallinity of the first metal organic framework.

[0043] Preferably, in preparing the first metal organic framework, the temperature of the solvothermal reaction is 80-150°C, for example, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C, etc.

[0044] Preferably, in the preparation of the first metal-organic framework, the solvent thermal reaction time is 15-20 h, for example, 15 h, 16 h, 17 h, 18 h, 19 h or 20 h, etc.

[0045] Preferably, in preparing the first metal-organic framework, the solvothermal reaction is carried out in a hydrothermal reactor.

[0046] Preferably, in the preparation of the first metal-organic framework, the product of the solvothermal reaction is also cooled after the solvothermal reaction.

[0047] Preferably, the separation method includes any one of centrifugation, filtration or suction filtration, preferably centrifugation.

[0048] Preferably, the centrifugal rotation speed is 6000-11000 r / min, for example 6000 r / min, 7000 r / min, 8000 r / min, 9000 r / min, 10000 r / min or 11000 r / min.

[0049] Preferably, in the process of preparing the first metal-organic framework, the separated solid product is further washed after the separation and before the drying.

[0050] Preferably, in the process of preparing the first metal organic framework, the solvent used for washing is any one of N,N-dimethylformamide, methanol or ethanol, or a combination of at least two of them.

[0051] Preferably, during the preparation of the first metal-organic framework, the drying method includes vacuum drying.

[0052] Preferably, during the preparation of the first metal-organic framework, the drying temperature is 60-100°C, such as 60°C, 70°C, 80°C, 90°C or 100°C.

[0053] As a preferred technical solution of the present invention, the preparation process of the platinum nanoparticle dispersion in step (1) comprises:

[0054] The platinum source is mixed with water for a second time to obtain a platinum source aqueous solution, and the platinum source aqueous solution is mixed with a stabilizer and a second solvent for a third time to obtain the platinum nanoparticle dispersion.

[0055] The platinum nanoparticle dispersion obtained by the synthesis of the present invention does not need to be subjected to other post-treatments, and the preparation process is simple. The stabilizer is added to prevent the aggregation of the nanoparticles.

[0056] Preferably, the concentration of the platinum source aqueous solution is 2-10mmol / L, for example, 2mmol / L, 3mmol / L, 4mmol / L, 5mmol / L, 6mmol / L, 7mmol / L, 8mmol / L, 9mmol / L or 10mmol / L.

[0057] In the present invention, the concentration of the intermediate platinum source aqueous solution in the preparation process of the platinum nanoparticle dispersion is regulated, thereby adjusting the content of platinum nanoparticles in the subsequent synthesis of the sandwich structure hydrogenation condensation catalyst, thereby ensuring the catalytic performance of the catalyst.

[0058] Preferably, the mass ratio of the stabilizer to the platinum element in the platinum source aqueous solution is (10-40):1, for example, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1 or 40:1, etc.

[0059] Preferably, the volume ratio of the second solvent to the platinum source aqueous solution is (8-10):1, for example 8:1, 8.5:1, 9:1, 9.5:1 or 10:1, etc.

[0060] Preferably, the platinum source includes any one of hexachloroplatinic acid, sodium hexachloroplatinate or potassium hexachloroplatinate, or a combination of at least two of them.

[0061] Preferably, the stabilizer includes any one of polyvinyl pyrrolidone, sodium citrate or sodium ascorbate, preferably polyvinyl pyrrolidone with an average relative molecular weight of 40,000.

[0062] Preferably, the second solvent comprises any one of methanol, ethanol or isopropanol or a combination of at least two thereof, preferably methanol.

[0063] The second solvent in the present invention also has the function of reducing the platinum source to prepare platinum nanoparticles.

[0064] Preferably, the third mixing is performed under oil bath conditions.

[0065] Preferably, the temperature of the third mixing is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0066] Preferably, the third mixing time is 1-6 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h or 6 h.

[0067] Preferably, after the third mixing, the product after the third mixing is further cooled.

[0068] As a preferred technical solution of the present invention, the preparation process of the precursor dispersion of the second metal organic framework in step (2) includes: mixing the second zirconium source, the second organic ligand and the third solvent for the fourth time to obtain the second precursor dispersion, and the second precursor dispersion is the precursor dispersion of the second metal organic framework.

[0069] In the present invention, the preparation order of the first metal organic framework, the platinum nanoparticle dispersion and the second metal organic framework precursor dispersion is not specific.

[0070] Preferably, the molar ratio of the second zirconium source to the second organic ligand is 3:(0.8-1.2), for example, 3:0.8, 3:0.9, 3:1, 3:1.1 or 3:1.2, etc.

[0071] Preferably, a second regulator is also added during the fourth mixing process.

[0072] Preferably, the volume ratio of the third solvent to the second regulator is 1:(0.2-1), such as 1:0.2, 1:0.4, 1:0.6, 1:0.8 or 1:1, etc.

[0073] Preferably, in the second precursor dispersion, the concentration of the second zirconium source is 10-30 mmol / L, for example, 10 mmol / L, 14 mmol / L, 18 mmol / L, 22 mmol / L, 26 mmol / L or 30 mmol / L.

[0074] Preferably, the second zirconium source includes any one of zirconium oxychloride octahydrate or zirconium tetrachloride, preferably zirconium oxychloride octahydrate.

[0075] Preferably, the second organic ligand comprises trimesic acid.

[0076] Preferably, the third solvent includes any one of N,N-dimethylformamide, N,N-diethylformamide or N,N-dimethylacetamide, preferably N,N-dimethylformamide.

[0077] Preferably, the second regulator comprises any one of formic acid, acetic acid or benzoic acid.

[0078] In a third aspect, the present invention provides a use of the sandwich-structured hydrogenation condensation catalyst as described in the first aspect, wherein the use comprises using the sandwich-structured hydrogenation condensation catalyst in a method for synthesizing imine compounds by catalyzing hydrogenation condensation reaction.

[0079] The present invention adopts a sandwich-structured hydrogenation condensation catalyst with a specific composition for catalyzing the hydrogenation condensation reaction to synthesize imine compounds. The sandwich-structured hydrogenation condensation catalyst has excellent stability, catalytic activity and selectivity, and can stably realize the successful preparation of imine compounds such as N-benzylideneaniline, and significantly improve the conversion rate of raw nitroaromatic compounds and aldehyde substrates and the yield of target product imine compounds.

[0080] Preferably, the method for synthesizing imine compounds by catalytic hydrogenation condensation reaction comprises the following steps:

[0081] Under a hydrogen atmosphere, the sandwich structure hydrogenation condensation catalyst is subjected to a first catalytic reaction with a nitroaromatic compound and a solvent in a reactor, and then cooled to obtain a mixed solution; then, the mixed solution is subjected to a second catalytic reaction with an aldehyde substrate, and the sandwich structure hydrogenation condensation catalyst is separated from the solid and liquid to obtain the imine compound.

[0082] The sandwich structure hydrogenation condensation catalyst used in the present invention has platinum nanoparticles evenly arranged in the interlayer between the inner and outer metal organic frameworks, which can efficiently catalyze the hydrogenation condensation reaction of nitro aromatic compounds and aldehyde substrates, and prepare the target imine compound product with high selectivity. In addition, the specific sandwich structure hydrogenation condensation catalyst can prevent the aggregation and shedding of platinum nanoparticles during use, improve the stability of the catalyst, so that the conversion efficiency and selectivity of the catalytic reaction of the catalyst remain basically unchanged after the catalyst is recycled for multiple times.

[0083] Preferably, the molar ratio of platinum atoms in the sandwich-structured hydrogenation condensation catalyst to the nitroaromatic compound is 1:(1000-10000), for example, 1:1000, 1:2000, 1:3000, 1:4000, 1:5000, 1:6000, 1:7000, 1:8000, 1:9000 or 1:10000, etc.

[0084] In the process of synthesizing imine compounds of the present invention, if the molar ratio of the platinum atoms in the sandwich-structured hydrogenation condensation catalyst to the nitroaromatic compound is too small, or too little catalyst is added, the conversion rate of the nitroaromatic compound will be too low; if the molar ratio of the two is too large, or too much catalyst is added, the conversion efficiency (TOF) will be reduced, and the selectivity of the imine compounds may also be reduced.

[0085] Preferably, the molar ratio of the nitroaromatic compound to the aldehyde substrate is (1-1.5):1, such as 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1, etc., preferably 1:1.

[0086] Preferably, the nitroaromatic compound includes any one of nitrobenzene and its derivatives, preferably nitrobenzene.

[0087] Preferably, the nitroaromatic compound includes any one of nitrobenzene, 2-fluoronitrobenzene, 3-fluoronitrobenzene or 4-fluoronitrobenzene, preferably nitrobenzene.

[0088] Preferably, the solvent includes any one of methanol, ethanol or isopropanol, or a combination of at least two of them.

[0089] Preferably, the aldehyde substrate comprises any one of benzaldehyde, 4-methoxybenzaldehyde, phenylacetaldehyde or phenylpropionaldehyde.

[0090] Preferably, when the obtained imine compound is N-benzylideneaniline, the nitroaromatic compound is nitrobenzene, and the aldehyde substrate is benzaldehyde.

[0091] Preferably, the first catalytic reaction is a high-pressure reaction carried out in a reactor.

[0092] Preferably, the temperature of the first catalytic reaction is 25-70°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C or 70°C, etc.

[0093] Preferably, the hydrogen pressure of the first catalytic reaction is 0.5-2 MPa, for example, 0.5 MPa, 1 MPa, 1.5 MPa or 2 MPa.

[0094] Preferably, the time of the first catalytic reaction is 0.2-3 h, for example, 0.2 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0095] Preferably, the first catalytic reaction is also accompanied by stirring.

[0096] Preferably, the stirring method is magnetic stirring.

[0097] Preferably, the second catalytic reaction is carried out at room temperature.

[0098] In the present invention, the "room temperature" refers to a temperature of 25±5°C, such as 20°C, 22°C, 24°C, 26°C, 28°C or 30°C.

[0099] Preferably, the second catalytic reaction time is 2-10 min, such as 2 min, 4 min, 6 min, 8 min or 10 min.

[0100] Compared with the prior art, the present invention has at least the following beneficial effects:

[0101] (1) The sandwich-structured hydrogenation condensation catalyst provided by the present invention disperses and encapsulates platinum nanoparticles in the interlayer of the first metal-organic framework and the second metal-organic framework, which is conducive to achieving firm encapsulation and orderly dispersion of the platinum nanoparticles, preventing the platinum nanoparticles from falling off or agglomerating, and improving the stability of the catalyst. In addition, the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst and the inner and outer metal-organic frameworks have a highly efficient synergistic effect, which can jointly improve the activity and selectivity of the catalyst, thereby making the catalyst have a better conversion efficiency (TOF).

[0102] (2) The preparation method provided by the present invention can ensure the uniform dispersion of platinum nanoparticles in the interlayer between the first metal organic framework and the second metal organic framework, which is conducive to enhancing the interaction between the platinum nanoparticles and the inner and outer metal organic frameworks, thereby preventing the platinum nanoparticles from falling off or agglomerating, achieving the firm encapsulation and orderly dispersion of the platinum nanoparticles, and improving the stability of the catalyst. The preparation method also has the advantages of convenient operation, simple equipment requirements, simple implementation, and excellent performance of the synthesized catalyst. The prepared catalyst can more conveniently achieve the synthesis of high conversion rate, high selectivity and high conversion efficiency of specific materials.

[0103] (3) In the process of catalyzing the hydrogenation condensation reaction to synthesize imine compounds, the sandwich-structured hydrogenation condensation catalyst has excellent stability, catalytic activity and selectivity, and can stably achieve the successful preparation of imine compounds such as N-benzylideneaniline, and significantly improve the conversion rate of the raw nitroaromatic compound and the aldehyde substrate and the yield of the target product imine compound. BRIEF DESCRIPTION OF THE DRAWINGS

[0104] Figure 1 This is a scanning electron microscope image of the first metal organic framework (MOF-808) in Example 1.

[0105] Figure 2 This is a transmission electron microscope image of the supported material (MOF-808@Pt) in Example 1.

[0106] Figure 3 This is a statistical diagram of the particle size of platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1.

[0107] Figure 4 This is a transmission electron microscope image of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1.

[0108] Figure 5 This is a partially enlarged transmission electron microscope image of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1.

[0109] Figure 6 This is a statistical chart of the outer layer thickness of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1.

[0110] Figure 7 X-ray diffraction patterns of the first metal organic framework (MOF-808) and the sandwich structure hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1.

[0111] Figure 8 Schematic diagram of the morphological changes during the preparation process of the sandwich-structured hydrogenation condensation catalyst in this example.

[0112] Among them, 1. the first metal organic framework; 2. the supporting material; 3. the sandwich structure hydrogenation condensation catalyst.

[0113] Fig. 9 This is a partially enlarged transmission electron microscope image of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 2.

[0114] Fig.10 This is a statistical chart of the outer layer thickness of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 2.

[0115] Fig.11 The figure is a schematic diagram of the process of synthesizing N-benzylidene aniline in the present invention.

[0116] Fig.12 This is a statistical graph of nitrobenzene conversion and N-benzylideneaniline selectivity during the catalytic synthesis of N-benzylideneaniline using the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Application Example 1 after 10 cycles. DETAILED DESCRIPTION

[0117] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0118] The average molecular weight of the stabilizer polyvinylpyrrolidone (PVP) used in the following examples is 40,000.

[0119] Example 1

[0120] The present embodiment provides a sandwich-structured hydrogenation condensation catalyst, which comprises, from the inside to the outside, an inner layer, an interlayer and an outer layer, wherein the inner layer is composed of a first metal organic framework, which is composed of MOF-808, has an octahedral morphology, and has an average diameter of 400 nm; the interlayer is provided with platinum nanoparticles, and the average particle size of the platinum nanoparticles is 2.2 nm, and the mass content is 0.6 wt %; the outer layer is composed of a second metal organic framework, which is composed of MOF-808, and the average thickness of the outer layer is 8 nm.

[0121] This embodiment also provides a method for preparing the above sandwich structured hydrogenation condensation catalyst, comprising the following steps:

[0122] (I) 578 mg of zirconium oxychloride octahydrate and 126 mg of trimesic acid were stirred and dispersed in a mixed solution of 18 mL of N,N-dimethylformamide and 18 mL of formic acid, and the solid matter was completely dissolved by ultrasonic dispersion to prepare a first precursor dispersion; then, the first precursor dispersion was transferred to a polytetrafluoroethylene hydrothermal autoclave liner, and loaded into a stainless steel hydrothermal autoclave, heated to 100° C. in a blast oven, and subjected to a solvent thermal reaction for 18 h, and then cooled to 25° C. and then taken out of the mixed solution, and centrifuged at a speed of 10000 r / min for 3 min to separate the solid product; then, the solid product was washed twice with 30 mL of N,N-dimethylformamide and deionized water, respectively, and centrifuged at a speed of 10000 r / min for 3 min; finally, the washed centrifuged product was dried in a vacuum drying oven at 80° C. for 12 h to obtain the first metal organic framework MOF-808 for standby use.

[0123] Take 0.12 mmol of hexachloroplatinic acid and disperse it in 20 mL of deionized water to obtain a hexachloroplatinic acid solution. Take 2 mL of the hexachloroplatinic acid solution, add 18 mL of methanol and 58.5 mg of polyvinyl pyrrolidone with an average molecular weight of 40,000, heat in an oil bath at 70°C for 3 hours, then take out after cooling, and prepare a platinum nanoparticle dispersion for use.

[0124] 107 mg of zirconium oxychloride octahydrate and 23.3 mg of trimesic acid were dissolved in 16.5 mL of N,N-dimethylformamide and 3.3 mL of formic acid to prepare a second precursor dispersion for later use.

[0125] (II) Take 100 mg of MOF-808 obtained in step (I), add 6 mL of the platinum nanoparticle dispersion obtained in step (I), and ultrasonically treat it for 30 min to allow it to fully adhere, then centrifuge it at a speed of 10000 r / min for 3 min to separate it, and dry the solid material in a vacuum drying oven at 80°C for 12 h to obtain a loaded material, which is the first metal organic framework MOF-808@Pt loaded with platinum nanoparticles.

[0126] (III) 100 mg of MOF-808@Pt obtained in step (II) was mixed with 30 mL of N,N-dimethylformamide and ultrasonically dispersed for 5 min. Subsequently, 5 mL of the second precursor dispersion obtained in step (I) was added and placed in a 250 mL round-bottom flask for mixing. The mixture was subjected to solvent thermal reaction in an oil bath at 100°C for 4 h. After cooling to 25°C, the mixed solution was taken out and centrifuged at 10000 r / min for 3 min to separate the solid product. Then, the mixture was washed with ethanol twice each and centrifuged at 10000 r / min for 3 min. Finally, the washed and centrifuged product was dried in a vacuum drying oven at 80°C for 12 h to prepare a sandwich structure hydrogenation condensation catalyst MOF-808@Pt@MOF-808.

[0127] Figure 1 : is a scanning electron microscope image of the first metal organic framework (MOF-808) in this embodiment. It can be seen from the figure that the morphology of the first metal organic framework (MOF-808) in this embodiment is octahedral, and its average diameter is about 400nm.

[0128] Figure 2 is a transmission electron microscope image of the supported material (MOF-808@Pt) in this example, Figure 3 This is a statistical diagram of the particle size of the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in this embodiment. It can be seen from the figure that the platinum nanoparticles are uniformly distributed on the first metal organic framework MOF-808 with an octahedral morphology, and the particle size of the platinum nanoparticles is in the range of 2.2±0.7nm.

[0129] Figure 4 and Figure 5 The transmission electron microscope images of the sandwich structure hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in this example are given. Figure 6 This is a statistical diagram of the outer layer thickness of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 1. It can be seen from the figure that the second metal organic framework (MOF-808) is coated on the support material (MOF-808@Pt), and its thickness is in the range of 7.9±1.7nm.

[0130] Figure 7 The X-ray diffraction patterns of the first metal organic framework (MOF-808) and the sandwich structure hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in this embodiment are shown in the figure. As can be seen from the figure, the X-ray diffraction patterns of the catalyst-loaded nanoparticles provided in this embodiment before and after the formation of the sandwich structure are similar to those of MOF-808. Figure 1 That is, the formation of the sandwich structure of MOF-808 coated with MOF-808 loaded with platinum nanoparticles did not change the crystal structure of MOF-808.

[0131] Figure 8 This is a schematic diagram of the morphological changes in the preparation process of the sandwich-structured hydrogenation condensation catalyst of this embodiment. As can be seen from the figure, the preparation process of the sandwich-structured hydrogenation condensation catalyst provided in this embodiment is achieved by uniformly loading platinum nanoparticles on an octahedral first metal-organic framework 1 to obtain a loaded material 2, and then coating the loaded material 2 to form a second metal-organic framework to obtain a sandwich-structured hydrogenation condensation catalyst 3.

[0132] Example 2

[0133] The difference between this embodiment and embodiment 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this embodiment, the average thickness of the outer second metal organic framework MOF-808 is 28nm. Accordingly, in the preparation method of the sandwich structure hydrogenation condensation catalyst provided in this embodiment, step (III) takes 100mg of MOF-808@Pt obtained in step (II) and 30mL of N,N-dimethylformamide, ultrasonically disperses for 5min, and then replaces it with adding 12mL of the second precursor dispersion obtained in step (I) and placing it in a round-bottom flask. The rest of the contents are the same as in embodiment 1.

[0134] Fig. 9 This is a partially enlarged transmission electron microscope image of the sandwich structure hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 2. Fig.10This is a statistical graph of the outer layer thickness of the sandwich-structured hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Example 2. It can be seen from the figure that the outer layer of MOF-808 in the sandwich-structured hydrogenation condensation catalyst prepared in this example is thicker than that in Example 1, and the outer layer thickness is in the range of 28.1±2.9nm.

[0135] Example 3

[0136] The difference between this embodiment and embodiment 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this embodiment, the content of the platinum nanoparticle interlayer is 0.2wt%, based on the total mass of the sandwich structure hydrogenation condensation catalyst being 100wt%. Accordingly, in the preparation method of the sandwich structure hydrogenation condensation catalyst provided in this embodiment, in step (II), 100mg of MOF-808 obtained in step (I) is added to 2mL of the platinum nanoparticle dispersion obtained in step (I). The rest of the contents are the same as those in embodiment 1.

[0137] Example 4

[0138] The difference between this embodiment and embodiment 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this embodiment, the content of the platinum nanoparticle interlayer is 2.0wt%, based on the total mass of the sandwich structure hydrogenation condensation catalyst being 100wt%. Accordingly, in the preparation method of the sandwich structure hydrogenation condensation catalyst provided in this embodiment, in step (II), 100mg of MOF-808 obtained in step (I) is taken and 20mL of the platinum nanoparticle dispersion obtained in step (I) is added. The rest of the contents are the same as those in embodiment 1.

[0139] Example 5

[0140] The difference between this embodiment and embodiment 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this embodiment, the outer metal organic framework is replaced with UiO-66. The rest of the contents are the same as those in embodiment 1.

[0141] Example 6

[0142] The difference between this embodiment and embodiment 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this embodiment, the metal organic frameworks of the inner layer and the outer layer are replaced with UiO-66. The rest of the contents are the same as those in embodiment 1.

[0143] Comparative Example 1

[0144] The difference between this comparative example and Example 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this comparative example, platinum nanoparticles are replaced with rhodium nanoparticles. Correspondingly, in the preparation method of the sandwich structure hydrogenation condensation catalyst provided in the comparative example, the preparation process of the platinum nanoparticle dispersion in step (I) is replaced by: taking 12.5 mg of rhodium trichloride trihydrate, dispersing it in 12.5 mL of deionized water, adding 112.5 mL of ethanol and 237.5 mg of polyvinyl pyrrolidone with an average molecular weight of 40,000, heating it in an oil bath at 76°C for 1.5 h, then taking it out after cooling, and preparing a rhodium nanoparticle dispersion. The rest of the contents are the same as in Example 1.

[0145] Comparative Example 2

[0146] The difference between this comparative example and Example 1 is that in the sandwich structure hydrogenation condensation catalyst provided in this comparative example, platinum nanoparticles and the outer second metal organic framework MOF-808 are omitted. Accordingly, in the preparation method of the catalyst provided in this comparative example, only the first metal organic framework MOF-808 is prepared. The rest of the contents are the same as in Example 1.

[0147] Comparative Example 3

[0148] The difference between this comparative example and Example 1 is that the outer second metal organic framework MOF-808 is omitted in the catalyst provided in this comparative example. Accordingly, in the preparation method of the catalyst provided in this comparative example, only the preparation of the first metal organic framework MOF-808 and the platinum nanoparticle dispersion in step (I) and the preparation of the first metal organic framework MOF-808@Pt loaded with platinum nanoparticles in step (II) are performed. The rest of the contents are the same as in Example 1.

[0149] Comparative Example 4

[0150] The difference between this comparative example and Example 1 is that the catalyst provided in this comparative example includes platinum nanoparticles supported on carbon materials. Accordingly, in the preparation method of the catalyst provided in this comparative example, 100 mg of carbon black powder is taken, 6 mL of the platinum nanoparticle dispersion described in Example 1 is added, ultrasonic treatment is performed for 30 min to allow it to fully adhere, and then centrifugation is performed at a speed of 10000 r / min for 3 min to separate, and the solid matter is washed twice with ethanol and dried in a vacuum drying oven at 80°C for 12 h to obtain a platinum nanoparticle catalyst supported on carbon materials. The rest of the contents are the same as Example 1.

[0151] Application Examples 1-6 and Comparative Application Examples 1-4

[0152] The sandwich structure hydrogenation condensation catalyst provided in Example 1-6 and the catalyst provided in Comparative Example 1-4 were placed in a reactor with 0.2 mmol nitrobenzene and 2 mL ethanol, and reacted for 30 min at 40° C., 1 MPa of hydrogen, and 600 r / min of magnetic stirring, and cooled to obtain a mixed solution, wherein the mass of the catalyst was 2 mg; then, the obtained mixed solution was taken out, 0.2 mmol benzaldehyde was added, and the reaction was carried out for 4 min at 25° C. with 600 r / min of magnetic stirring; then, the reaction solution was centrifuged at a speed of 10000 r / min for 3 min to separate the added catalyst, and synthesized N-benzylidene aniline was obtained. The specific schematic diagram of the catalytic synthesis reaction of N-benzylidene aniline is shown as follows: Fig.11 shown.

[0153] The conversion rate of nitrobenzene and the selectivity of N-benzylidene aniline and the conversion efficiency (TOF) of the catalyst in the process of synthesizing N-benzylidene aniline in Example 1-6 and Comparative Application Example 1-4 were calculated and recorded, and the results are shown in Table 1.

[0154] Table 1

[0155] Group Nitrobenzene conversion rate (%) N-benzylideneaniline selectivity (%) <![CDATA[TOF(h -1 )]]> Application Example 1 >99 >99 6500 Application Example 2 64 91 4160 Application Example 3 15 23 2925 Application Example 4 >99 87 1950 Application Example 5 49 53 3185 Application Example 6 34 31 2210 Comparative application example 1 3 42 195 Comparative Application Example 2 0 - 0 Comparative Application Example 3 69 89 4485 Comparative Application Example 4 62 77 4030

[0156] The process of catalyzing the synthesis of N-benzylideneaniline using the catalyst in Example 1 and Comparative Application Example 3 was repeated 10 times. The catalyst after each catalysis was collected and washed twice with ethanol, dried in air and then continued to be used. The conversion rate of nitrobenzene and the selectivity of N-benzylideneaniline in the first and fifth repeated cycles of the catalytic synthesis process were recorded. The results are shown in Table 2.

[0157] Table 2

[0158]

[0159]

[0160] Application Example 7-11

[0161] The sandwich structure hydrogenation condensation catalyst provided in Example 1 is placed in a reactor with 0.2 mmol of a nitro aromatic compound and 2 mL of ethanol, and reacted for a certain period of time at 40°C, 1 MPa of hydrogen, and accompanied by magnetic stirring at 600 r / min, and cooled to obtain a mixed solution, wherein the amount of the sandwich structure hydrogenation condensation catalyst used is 2 mg; then, the obtained mixed solution is taken out, 0.2 mmol of an aldehyde substrate is added, and the reaction is carried out at 25°C with magnetic stirring at 600 r / min for 4 min; then the reaction solution is centrifuged at a speed of 10000 r / min for 3 min to separate the added catalyst to obtain an imine compound.

[0162] Among them, the aldehyde substrate used in Application Examples 7-9 is still benzaldehyde, but the nitroaromatic compound used in Application Example 7 is 2-fluoronitrobenzene, the nitroaromatic compound used in Application Example 8 is 3-fluoronitrobenzene, and the nitroaromatic compound used in Application Example 9 is 4-fluoronitrobenzene; the nitroaromatic compound used in Application Examples 10 and 11 is still nitrobenzene, but the aldehyde substrate used in Application Example 10 is phenylpropionaldehyde, and the aldehyde substrate used in Application Example 11 is 4-methoxybenzaldehyde. The above results are shown in Table 3.

[0163] Table 3

[0164]

[0165] The test results show that:

[0166] (1) It can be seen from Application Example 1 that the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst provided by the present invention interact with the metal organic frameworks in the inner and outer layers, thereby preventing the platinum nanoparticles from falling off or agglomerating, thereby improving the stability of the catalyst. In addition, the synergistic effect of the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst and the metal organic frameworks in the inner and outer layers jointly improves the activity and selectivity of the catalyst, thereby making the catalyst have a more excellent conversion efficiency (TOF).

[0167] Fig.12 The nitrobenzene conversion rate and selectivity of N-benzylidene aniline in the process of synthesizing N-benzylidene aniline by 10 cycles of the sandwich structure hydrogenation condensation catalyst (MOF-808@Pt@MOF-808) in Application Example 1 are shown in FIG. Fig.12 It can be seen that the sandwich-structured hydrogenation condensation catalyst obtained in Application Example 1 maintained substantially complete conversion of substrate aniline and more than 99% selectivity for N-benzylidene aniline during 10 cycles of testing, indicating that the obtained catalyst has excellent stability.

[0168] (2) By comparing Application Example 1 with Application Example 2, it can be seen that if the thickness of the outer layer in the present invention is too thick, it will hinder the mass transfer of the substrate to the platinum nanoparticles, and the catalytic performance of the obtained catalyst will be significantly reduced. In addition, in the preparation method of the sandwich structure hydrogenation condensation catalyst of the present invention, the volume ratio of the support material dispersion liquid to the second metal organic framework precursor dispersion liquid will affect the thickness of the outer layer of the sandwich structure hydrogenation condensation catalyst finally obtained, thereby affecting the activity, selectivity and stability of the sandwich structure hydrogenation condensation catalyst.

[0169] (3) By comparing Application Example 1 with Application Examples 3 and 4, it can be seen that if the volume mass ratio of the platinum nanoparticle dispersion to the first metal organic framework in the present invention is too low, the content of the platinum nanoparticles is low, which will lead to poor catalytic performance of the catalyst; if the volume mass ratio of the two is too high, it will induce aggregation of the platinum nanoparticles and affect the imine selectivity.

[0170] (4) By comparing Application Example 1 with Application Examples 5 and 6, it can be seen that in the sandwich structure hydrogenation condensation catalyst of the present invention, if the outer metal organic framework adopts UiO-66, the conversion rate of nitrobenzene and the imine selectivity will be significantly reduced; if the inner and outer layers of the sandwich structure hydrogenation condensation catalyst are both composed of UiO-66, the catalytic performance will be further reduced, indicating that both the inner and outer MOF-808 layers have an important promoting effect on the catalytic activity and imine selectivity.

[0171] (5) By comparing Application Example 1 with Comparative Application Example 1, it can be seen that if the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst of the present invention are replaced with rhodium nanoparticles, the catalyst will have almost no catalytic hydrogenation activity, indicating that platinum nanoparticles have significantly better catalytic performance than other metal nanoparticles.

[0172] (6) By comparing Application Example 1 with Comparative Application Example 2, it can be seen that if only the inner layer of the MOF-808 metal organic framework constitutes the catalyst of the present invention, and the platinum nanoparticles and the outer layer of the MOF-808 metal organic framework are omitted, the conversion rate of nitrobenzene in the process of synthesizing N-benzylideneaniline will be 0, indicating that the active site for catalyzing the hydrogenation reaction of nitrobenzene is the platinum nanoparticles.

[0173] (7) By comparing Application Example 1 with Comparative Application Example 3, it can be seen that if the catalyst of the present invention is composed only of an inner layer MOF-808 metal organic framework and an interlayer of platinum nanoparticles, and the outer layer MOF-808 metal organic framework is omitted, the catalytic activity and selectivity of the catalyst will decrease, indicating that the interfacial interaction between the platinum nanoparticles and the outer layer MOF-808 is beneficial to optimizing the catalytic activity and selectivity of the hydrogenation condensation reaction; by comparing the cyclic reaction catalytic test results, it can be seen that the presence of the outer layer MOF-808 also plays a vital role in maintaining the cyclic stability of the catalyst, which illustrates the firm encapsulation and effective dispersion of the platinum nanoparticles by the outer layer MOF-808.

[0174] (8) By comparing Application Example 1 with Comparative Application Example 4, it can be seen that if the present invention only uses platinum nanoparticles that are not encapsulated by a zirconium-based metal organic framework as a catalyst, the conversion rate of nitrobenzene and the selectivity of N-benzylideneaniline will be low, and the conversion efficiency of the catalyst will be reduced. This shows that the presence of the inner and outer metal organic frameworks is beneficial to improving the catalytic hydrogenation activity of platinum nanoparticles, and is also beneficial to optimizing the imine selectivity and improving the conversion efficiency of the catalyst.

[0175] (9) It can be seen from the results of Application Examples 1 and 7-11 that the sandwich-structured hydrogenation condensation catalyst provided by the present invention can not only catalyze the hydrogenation condensation reaction of nitrobenzene and benzaldehyde to achieve high conversion efficiency and high selectivity in the preparation of N-benzylidene aniline, but can also be expanded to be used in the preparation of various imine compounds with various nitroaromatic compounds and aldehyde substrates as raw materials, and has good substrate universality.

[0176] In summary, the sandwich-structured hydrogenation condensation catalyst provided by the present invention disperses and encapsulates platinum nanoparticles in the interlayer of the first metal-organic framework and the second metal-organic framework, which is conducive to achieving firm encapsulation and orderly dispersion of the platinum nanoparticles, preventing the platinum nanoparticles from falling off or agglomerating, thereby improving the stability of the catalyst. In addition, the platinum nanoparticles in the sandwich-structured hydrogenation condensation catalyst and the inner and outer metal-organic frameworks have a highly efficient synergistic effect, which can jointly improve the activity and selectivity of the catalyst, thereby making the catalyst have a more excellent conversion efficiency (TOF).

[0177] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A sandwich structured hydrocondensation catalyst, characterized in that: The sandwich-structured hydrogenation condensation catalyst comprises an inner layer, an interlayer and an outer layer from the inside to the outside; the inner layer comprises a first metal organic framework, the interlayer comprises platinum nanoparticles, and the outer layer comprises a second metal organic framework.

2. The sandwich structure hydrocondensation catalyst according to claim 1, characterized in that: The first metal organic framework and the second metal organic framework each independently comprise a zirconium-based metal organic framework material; Preferably, the first metal organic framework and the second metal organic framework are the same, preferably MOF-808.

3. The sandwich structure hydrocondensation catalyst according to claim 1 or 2, characterized in that: The microscopic morphology of the first metal organic framework of the inner layer is an octahedron, and the diameter of the octahedron is 300-500nm; Preferably, the average particle size of the platinum nanoparticles is 1-3 nm, preferably 1.7-2.8 nm; Preferably, based on the total mass of the sandwich structure hydrogenation condensation catalyst being 100wt%, the mass percentage of the platinum nanoparticles is 0.2-2wt%, preferably 0.4-1.8wt%; Preferably, the thickness of the outer layer is 5-40 nm, preferably 5-20 nm.

4. A method for preparing a sandwich structure hydrogenation condensation catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing a platinum nanoparticle dispersion with a first metal organic framework, and drying the mixture to obtain a supported material, wherein the supported material includes the first metal organic framework supported with platinum nanoparticles; (2) Mixing the support material with a solvent to obtain a support material dispersion, subjecting the support material dispersion to a solvent thermal reaction with a second metal organic framework precursor dispersion, and then separating and drying to obtain the sandwich structure hydrogenation condensation catalyst.

5. The preparation method according to claim 4, characterized in that: The volume mass ratio of the platinum nanoparticle dispersion in step (1) to the first metal organic framework is 1 mL: (10-50) mg; Preferably, the mixing time in step (1) is 15-60 min; Preferably, the concentration of the load material dispersion in step (2) is 2-10 mg / mL; Preferably, the volume ratio of the support material dispersion liquid to the second metal organic framework precursor dispersion liquid in step (2) is (1-8):1, preferably (3-6):1; Preferably, the temperature of the solvent thermal reaction in step (2) is 80-150°C; Preferably, the solvent thermal reaction time in step (2) is 15-20 hours.

6. The preparation method according to claim 4 or 5, characterized in that: Step (1) The preparation process of the first metal organic framework comprises: A first zirconium source, a first organic ligand and a first solvent are first mixed to obtain a first precursor dispersion, the first precursor dispersion is subjected to a solvothermal reaction, and then separated and dried to obtain the first metal organic framework; Preferably, the molar ratio of the first zirconium source to the first organic ligand is 3:(0.8-1.2); Preferably, a first regulator is also added during the first mixing process; Preferably, the volume ratio of the first solvent to the first regulator is 1:(0.2-1); Preferably, in the first precursor dispersion, the concentration of the first zirconium source is 10-100 mmol / L; Preferably, the first zirconium source comprises any one of zirconium oxychloride octahydrate or zirconium tetrachloride, preferably zirconium oxychloride octahydrate; Preferably, the first organic ligand comprises trimesic acid; Preferably, in preparing the first metal organic framework, the temperature of the solvothermal reaction is 80-150°C; Preferably, in the preparation of the first metal-organic framework, the solvent thermal reaction time is 15-20 hours.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The preparation process of the platinum nanoparticle dispersion in step (1) comprises: Mixing the platinum source with water for a second time to obtain a platinum source aqueous solution, and mixing the platinum source aqueous solution with a stabilizer and a second solvent for a third time to obtain the platinum nanoparticle dispersion; Preferably, the concentration of the platinum source aqueous solution is 2-10 mmol / L; Preferably, the mass ratio of the stabilizer to the platinum element in the platinum source aqueous solution is (10-40):1; Preferably, the volume ratio of the second solvent to the platinum source aqueous solution is (8-10):1; Preferably, the second solvent comprises any one of methanol, ethanol or isopropanol or a combination of at least two thereof, preferably methanol; Preferably, the third mixing is performed under oil bath conditions; Preferably, the temperature of the third mixing is 50-80°C; Preferably, the third mixing time is 1-6 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: Step (2) The preparation process of the precursor dispersion of the second metal organic framework comprises: mixing the second zirconium source, the second organic ligand and the third solvent for a fourth time to obtain a second precursor dispersion, wherein the second precursor dispersion is the precursor dispersion of the second metal organic framework; Preferably, the molar ratio of the second zirconium source to the second organic ligand is 3:(0.8-1.2); Preferably, a second regulator is also added during the fourth mixing process; Preferably, the volume ratio of the third solvent to the second regulator is 1:(0.2-1); Preferably, in the second precursor dispersion, the concentration of the second zirconium source is 10-30 mmol / L; Preferably, the second zirconium source includes any one of zirconium oxychloride octahydrate or zirconium tetrachloride, preferably zirconium oxychloride octahydrate; Preferably, the second organic ligand comprises trimesic acid; Preferably, the third solvent includes any one of N,N-dimethylformamide, N,N-diethylformamide or N,N-dimethylacetamide, preferably N,N-dimethylformamide.

9. Use of the sandwich structure hydrocondensation catalyst according to any one of claims 1 to 3, characterized in that: The use includes using the sandwich structured hydrogenation condensation catalyst in a method for synthesizing imine compounds through catalytic hydrogenation condensation reaction.

10. The use according to claim 9, characterized in that The method for synthesizing imine compounds by catalytic hydrogenation condensation reaction comprises the following steps: Under a hydrogen atmosphere, the sandwich structure hydrogenation condensation catalyst is subjected to a first catalytic reaction with a nitro aromatic compound and a solvent, and cooled to obtain a mixed solution; then, the mixed solution is subjected to a second catalytic reaction with an aldehyde substrate, and the sandwich structure hydrogenation condensation catalyst is separated from the solid and liquid to obtain the imine compound; Preferably, the molar ratio of the platinum atom in the sandwich structure hydrogenation condensation catalyst to the nitro aromatic compound is 1:(1000-10000); Preferably, the molar ratio of the nitroaromatic compound to the aldehyde substrate is (1-1.5):1; Preferably, the nitroaromatic compound includes any one of nitrobenzene and its derivatives, preferably nitrobenzene; Preferably, the aldehyde substrate comprises any one of benzaldehyde, 4-methoxybenzaldehyde, phenylacetaldehyde or phenylpropionaldehyde, preferably benzaldehyde; Preferably, when the obtained imine compound is N-benzylideneaniline, the nitroaromatic compound is nitrobenzene, and the aldehyde substrate is benzaldehyde; Preferably, the temperature of the first catalytic reaction is 25-70°C; Preferably, the hydrogen pressure of the first catalytic reaction is 0.5-2MPa; Preferably, the time of the first catalytic reaction is 0.2-3h; Preferably, the first catalytic reaction is also accompanied by stirring; Preferably, the second catalytic reaction is carried out at room temperature; Preferably, the second catalytic reaction time is 2-10 min.

Citation Information

Patent Citations

  • Synthetic method of N-benzylideneaniline compound

    CN103214392A